The importance of studying history of medicine and language training for the development of professional competencies of medical students. - L. S Semyonova; I. N. Klimenko (Medičnì Perspektivi)
This article shows the importance of studying history of medicine and importance of language training as an essential component of broadening of universal cultural and medical outlook of prospective doctors, upbringing of high moral ethical qualities inherent to a contemporary doctor. The authors of the article propose measure on improving teaching of these disciplines.